Comparison of glaucoma progression rate in glaucoma patients at different stages using guided progression analysis with optical coherence tomography - Okan Akmaz; Murat Gokhan Tokac; Murat Garli; Tuncay Kusbeci (BMC Ophthalmology)
Abstract Background The aim of the present study was to compare the rates of change in Ganglion Cell- Inner Plexiform Layer (GCIPL) and Retinal Nerve Fiber Layer (RNFL) thickness, as measured by Optical Coherence Tomography (OCT) Guided Progression Analysis (GPA) program in control group, Primary Open Angle Glaucoma (POAG) and Pseudoexfoliation Glaucoma (PXG) eyes. Methods 60 POAG and 60 PXG patients and 30 control group patients were included in the study. Patients diagnosed with glaucoma were divided into two groups as mild (Mean deviation (MD) > -6.00) and moderate-severe (MD < -6.00). The average, superior and inferior quadrant thinning rates (expressed in micrometers per year) of GCIPL and RNFL in the OCT GPA program were compared between groups. Results Average GCIPL thinning rates were -0.23 ± 0.21 μm/year in the control group, -0.64 ± 0.54 μm/year in POAG patients, and -1.06 ± 1.16 μm/year in PXG patients (ANOVA, p < 0.001). Average RNFL thinning rates were -0.33 ± 0.44 μm/year in the control group, -0.86 ± 0.73 μm/year in POAG patients, and -1.33 ± 1.4 μm/year in PXG patients (ANOVA, p < 0.001). Conclusions The rates of GCIPL and RNFL thinning were highest in patients with PXG. We found that the glaucoma stage did not affect the rate of RNFL and GCIPL thinning.